Immunoprophylactic and immunotherapeutic control of hormone receptor-positive breast cancer - Buqué, Aitziber; Bloy, Norma; Perez-Lanzón, Maria; Iribarren, Kristina; Humeau, Juliette; Pol, Jonathan G; Levesque, Sarah; Mondragon, Laura; Yamazaki, Takahiro; Sato, Ai; Aranda, Fernando; Durand, Sylvère; et al. (Nature communications, 2020)
Hormone receptor (HR)+ breast cancer (BC) causes most BC-related deaths, calling for improved therapeutic approaches. Despite expectations, immune checkpoint blockers (ICBs) are poorly active in patients with HR+ BC, in part reflecting the lack of preclinical models that recapitulate disease progression in immunocompetent hosts. We demonstrate that mammary tumors driven by medroxyprogesterone acetate (M) and 7,12-dimethylbenz[a]anthracene (D) recapitulate several key features of human luminal B HR+HER2- BC, including limited immune infiltration and poor sensitivity to ICBs. M/D-driven oncogenesis is accelerated by immune defects, demonstrating that M/D-driven tumors are under immunosurveillance. Safe nutritional measures including nicotinamide (NAM) supplementation efficiently delay M/D-driven oncogenesis by reactivating immunosurveillance. NAM also mediates immunotherapeutic effects against established M/D-driven and transplantable BC, largely reflecting increased type I interferon secretion by malignant cells and direct stimulation of immune effector cells. Our findings identify NAM as a potential strategy for the prevention and treatment of HR+ BC.
Keywords: Animals; nádory prsu; Female; 9,10-Dimethyl-1,2-benzanthracene; ženské pohlaví; Mice, Knockout; myši knockoutované; Immunotherapy; lidé; niacinamid; Survival Analysis; Interferon Type I; Mammary Neoplasms, Experimental; Breast Neoplasms; Mice, Inbred BALB C; Carcinogenesis; interferon typ I; Niacinamide; karcinogeneze; Receptor, ErbB-2; Humans; receptor erbB-2; 9,10-dimethyl-1,2-benzanthracen; progrese nemoci; imunoterapie; myši inbrední BALB C; Disease Progression; analýza přežití; Medroxyprogesterone Acetate; zvířata; Mice, Inbred C57BL; medroxyprogesteronacetát; myši inbrední C57BL; experimentální nádory mléčných žláz